Implementing advance care plans in the peri‐operative period, including plans for cardiopulmonary resuscitation: Association of Anaesthetists clinical practice guideline. (15th February 2022) - Meek, T.; Clyburn, R.; Fritz, Z.; Pitcher, D.; Ruck Keene, A.; Young, P. J.
Summary: Contemporary guidance takes a patient‐centred approach and recommends discussing and planning treatments that should be considered, not just those that should be withheld. Although some organisations and communities still use specific DNACPR (do not attempt cardiopulmonary resuscitation) forms to recommend that cardiopulmonary resuscitation is not attempted, this approach has been shown to have disadvantages and is no longer regarded as best practice. The following guidelines have been produced in response to this change. They are designed to help anaesthetists, as part of the wider healthcare team, to implement and respond to advance care planning documents before and during procedures. The guidelines apply to all procedures, however minor and low risk they are considered to be, and the same ethical and legal principles apply to procedures carried out under local or regional anaesthesia and/or conscious sedation, as well as to those under general anaesthesia.